Relationship between physical activity level, leisure sedentary time, and frailty among residents aged 30 – 79 years in Wuzhong district, Suzhou city: a baseline surveillance data analysis - Xikang FAN; Jiang HUA; Jian SU; Hao YU; Yan LU; Yujie HUA; Jianrong JIN; Pei PEI; Dianjianyi SUN; Canqing YU; Jun LYU; Jinyi ZHOU; et al. (Zhongguo gonggong weisheng)
ObjectiveTo investigate the relationship between physical activity level, leisure sedentary time, and frailty among residents aged 30 – 79 years in Wuzhong district, Suzhou city, Jiangsu province, and to provide a reference for the prevention and control of frailty among local residents. MethodsData were collected from 53 269 residents aged 30 – 79 years in Wuzhong district, Suzhou city, who participated in the baseline survey of the China Kadoorie Biobank (CKB) from November 2004 to January 2008. An unordered multinomial logistic regression model was used to analyze the relationship between physical activity level, leisure sedentary time, and pre-frailty and frailty. ResultsOf the 53 269 residents aged 30 – 79 years in Wuzhong district, Suzhou city, 23 096 (43.36%) were pre-frail and 1 227 (2.30%) were frail. The physical activity levels were categorized as follows: < 12.73 MET-h/d (13,315 participants, 25.00%), 12.73 – 23.19 MET-h/d (13 319 participants, 25.00%), 23.20 – 37.29 MET-h/d (13 311 participants, 24.99%), and ≥ 37.30 MET-h/d (13 324 participants, 25.01%). Leisure sedentary time was categorized as follows: 0 – 2 h/d (24 631 participants, 46.23%), 3 – 4 h/d (20 028 participants, 37.61%), 5 – 6 h/d (5 764 participants, 10.82%), and ≥ 7 h/d (2 846 participants, 5.34%). After adjusting for confounding factors such as sex, age, education level, marital status, annual household income, smoking status, alcohol consumption, frequency of fresh vegetable intake, frequency of fresh fruit intake, and frequency of red meat intake, the results of unordered multinomial logistic regression analysis showed that compared with residents with a physical activity level of < 12.73 MET-h/d, the risk of pre-frailty was 0.76 times lower (OR = 0.76, 95%CI = 0.72 – 0.80), 0.67 times lower (OR = 0.67, 95%CI = 0.63 – 0.71), and 0.66 times lower (OR = 0.66, 95%CI = 0.62 – 0.69) for those with physical activity levels of 12.73 – 23.19 MET-h/d, 23.20 – 37.29 MET-h/d, and ≥ 37.30 MET-h/d, respectively. The risk of frailty was 0.50 times lower (OR = 0.50, 95%CI = 0.43 – 0.59), 0.35 times lower (OR = 0.35, 95%CI = 0.29 – 0.43), and 0.29 times lower (OR = 0.29, 95%CI = 0.23 – 0.36), respectively. Compared with residents with a leisure sedentary time of 0 – 2 h/d, the risk of pre-frailty was 1.10 times higher (OR = 1.10, 95%CI = 1.06 – 1.14), 1.33 times higher (OR = 1.33, 95%CI = 1.25 – 1.41), and 1.61 times higher (OR = 1.61, 95%CI = 1.48 – 1.76) for those with leisure sedentary times of 3 – 4 h/d, 5 – 6 h/d, and ≥ 7 h/d, respectively. The risk of frailty was 1.57 times higher (OR = 1.57, 95%CI = 1.30 – 1.89) and 2.65 times higher (OR = 2.65, 95%CI = 2.17 – 3.24) for those with leisure sedentary times of 5 – 6 h/d and ≥ 7 h/d, respectively. ConclusionsPhysical activity level was negatively correlated with frailty, while leisure sedentary time was positively correlated with frailty among residents aged 30 – 79 years in Wuzhong district, Suzhou city.